Substance Abuse and BMI Are Associated with Increased Inflammation and Oxidative Stress in Participants of the Miami Adult Studies on HIV (MASH) Cohort. (29th May 2020) - Gonzalez, Nicholas; Hernandez, Jacqueline; Teeman, Colby; Huang, Yongjun; Rodriguez, Jose Bastida; Martinez, Sabrina Sales; Campa, Adriana; Seminario, Leslie; Jasmin, Jupshy; Johnson, Angelique; Tamargo, Javier; Baum, Marianna
Abstract: Objectives: Inflammation and oxidative stress are considered important factors in the development of non-communicable diseases with aging. We determined associations between body mass index (BMI), oxidative stress (OS), and inflammation in people living with HIV (PLWH) and un-infected substance users. Methods: Overweight/obesity (OW/OB) was defined as BMI ≥ 25 and normal weight (NW) as BMI ≤ 24.9 in participants of the MASH cohort. Cocaine use was assessed with questionnaires and urine toxicology. Smoking was assessed with questionnaires. Blood was collected to assess inflammation (high sensitivity C-reactive protein [hsCRP] >3 m/L) by LabCorp, and OS with ARBOR ASSAYS (Ann Arbor, MI) glutathione colorimetric detection kit with %oxidized glutathione above median (>2.33%) as elevated. HIV viral load (VL) was obtained from medical charts. Regressions compared substance-abusing PLWH and un-infected people and controlled for age, sex, HIV status, and BMI. Results: Mean age of the 605 participants was 54.4 ± 7.4 years, 54.7% male, 70.1% Black; 76% were OW/OB; 73% used cocaine and smoked cigarettes. PLWH comprised 45.5% of the population and 75% had suppressed VL. Regardless of HIV status, OW/OB cocaine users had higher odds for inflammation (OR = 3.1, 95% CI: 1.7–5.6, P < 0.001) and higher OS (OR = 2.0, 95% CI: 1.1–3.4, P = 0.018) than NW cocaine users. OW/OB cocaine + cigarette users also had higher odds for inflammation (OR = 2.6, 95% CI: 1.6–4.2, P = 0.001) and higher OS (OR = 1.9, 95% CI: 1.2–2.9, P = 0.006) than NW cocaine + cigarette users. There were no differences in inflammation or OS between OW/OB cocaine alone or with cigarette use and non-users ( P = 0.707). HIV status was not independently associated with inflammation or high OS ( P > 0.33). Conclusions: These results indicated that OW/OB is associated with higher levels of inflammation and oxidative stress than normal weight even when accompanied with cocaine use as well as cocaine + cigarette use. These findings suggest that the use of substances does not increase inflammation or OS beyond overweight/obesity. In addition, in this cohort, with largely suppressed VL, HIV status was not independently associated with greater inflammation or OS. OW/OB is prevalent among PLWH and healthy people and may play an important role in the development of non-communicable diseases. Funding Sources: National Institute on Drug Abuse.